2020
DOI: 10.1177/0020872820940017
|View full text |Cite
|
Sign up to set email alerts
|

Examining COVID-19 and HIV: The impact of intersectional stigma on short- and long-term health outcomes among African Americans

Abstract: The COVID-19 pandemic has exacerbated the health disparities and structural racism among African Americans. We examined overlaps between the COVID-19 pandemic and HIV epidemic using an intersectional stigma framework through the lens of Critical Race Theory. Intersectional stigma, medical mistrust, and decreased likelihood of referral for HIV and COVID-19 testing leads to decreased engagement in the healthcare system. Social inequities increase health disparities and lead to increased rates of chronic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Many editorials explicitly considered the disparity in COVID-19 related outcomes for PLHIV among ethnic and racial minorities, but only four studies investigated this directly. African American and Latinx PLHIV in the US are showing disproportionate rates of COVID-19 infection and mortality, as well as increased levels of homelessness and unemployment [9,35,56,57]. Furthermore, mistrust of government sources, notably the President and elected officials, has the potential to cause treatment and vaccine hesitancy in minority populations, paralleling the HIV epidemic [29,35,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many editorials explicitly considered the disparity in COVID-19 related outcomes for PLHIV among ethnic and racial minorities, but only four studies investigated this directly. African American and Latinx PLHIV in the US are showing disproportionate rates of COVID-19 infection and mortality, as well as increased levels of homelessness and unemployment [9,35,56,57]. Furthermore, mistrust of government sources, notably the President and elected officials, has the potential to cause treatment and vaccine hesitancy in minority populations, paralleling the HIV epidemic [29,35,45].…”
Section: Discussionmentioning
confidence: 99%
“…Many inequalities related to poor health outcomes, stigma and discrimination have been magnified through COVID-19 and highlighted in editorials, particularly those penned in the US [2,[56][57][58][59]. Authors drew attention to African American PLHIV, who have been disproportionately affected by COVID-19 and are more likely to develop health complications, experience homelessness, unemployment, poverty and/or disadvantage associated with the costs of health care [2,17,42,[56][57][58][59]. The challenges faced by women living with HIV (WLHIV) were rarely explored within the primary research literature; however Closson et al's [60] editorial sought to draw attention to WLHIV's increased risk of domestic violence as a result of stay-at-home measures.…”
Section: Racial and Social Inequality Stigma And Discriminationmentioning
confidence: 99%
“…The unparalleled COVID-19 pandemic has intensified the stigma, marginalization, and structural racism that was already devastating African American communities [ 80 ]. Stigma has been described as an experience of individuals or communities who are purposely or inevitably excluded from full social approval or who have something unusual or unpleasant exposed about their moral status [ 81 ].…”
Section: Social Stigma and Covid-19mentioning
confidence: 99%
“…Furthermore, addressing health disparities will require a multifaceted approach from diverse stakeholders, including academic institutions [ 144 ]. Therefore, solutions are needed to enhance community engagement among stakeholders of African American health, augment population and public health funding to promote health equity among African Americans, and increase the number of African American healthcare providers [ 80 ]. These efforts may help mitigate the negative effects of hierarchy of citizenship [ 12 ] that exist among communities of color in the U.S.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Over 50 countries have implemented national policies or issued guidelines recommending PrEP for populations at high risk of HIV acquisition (Hodges-Mameletzis et al 2018), yet health inequalities, linked to PrEP provision and uptake, persist and research has shown that these are likely to be exacerbated by the effects of COVID-19 (Nydegger and Hill 2020). This study has investigated the news coverage in the U.S. and the U.K. & Ireland to consider how PrEPand issues of uneven provision of the treatmentare reported, considering how media messages reflect ideologies that can lead to stigmatisation and discourage those who need the treatment from seeking it.…”
Section: Discussionmentioning
confidence: 99%